2018
DOI: 10.1123/ijatt.2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers’ Perceived Challenges Toward Comprehensive Concussion Management in the Secondary School Setting

Abstract: Available financial and personnel resources often dictate the specifics of concussion policies and procedures in the secondary school setting. The purpose of this qualitative study was to explore athletic trainers' perceived challenges toward comprehensive concussion management in the secondary school setting. The findings indicate several challenges exist toward concussion management in the secondary school, including facility, personnel, and community resources, education levels of various stakeholders, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, this may have been due to a lack of communication or understanding among the student-athlete and/or members of the concussion management team. 57 Regardless, it highlights one area where improved communication and postinjury education may be required to ensure that the patient, family, and medical and school personnel are on the same page.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may have been due to a lack of communication or understanding among the student-athlete and/or members of the concussion management team. 57 Regardless, it highlights one area where improved communication and postinjury education may be required to ensure that the patient, family, and medical and school personnel are on the same page.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that while concussion education has made significant strides in the last few years, improvements are still needed. Efforts should be focused on educating student–athletes, parents, school staff, and personnel, particularly in areas with less access to community resources ( Welch Bacon, Cohen, Kay, Tierney, & Valovich McLeod, 2018 ). In a recent study, Welch Bacon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts should be focused on educating student–athletes, parents, school staff, and personnel, particularly in areas with less access to community resources ( Welch Bacon, Cohen, Kay, Tierney, & Valovich McLeod, 2018 ). In a recent study, Welch Bacon et al. (2018) found that athletic trainers reported similar challenges with a lack of education from coaches and parents, which hindered their ability to properly manage concussions at the secondary school level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations